Niobium titanic acid membrane catalytic material for efficiently synthesizing acetate spices at room temperature

The preparation of niobium titanate film catalytic material through high temperature calcination and acid treatment steps is solved, and the problems of high reaction temperature, long reaction time and low conversion rate in the preparation process of benzyl acetate in the prior art are achieved, and the efficient synthesis of acetate fragrances at room temperature is achieved, and the reaction conversion rate can reach 100%.

CN119565589APending Publication Date: 2025-03-07TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410181065.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-02-18
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art has problems such as high reaction temperature, long reaction time, low reactant conversion rate and complex catalyst treatment when preparing benzyl acetate, which hinders the industrial production of benzyl acetate.

Method used

Potassium niobium titanate mass was synthesized by high-temperature calcination, and then niobium titanate nanosheets were separated by acid treatment and organic alkali intercalation. Then, a catalytic material of niobium titanate film was prepared by vacuum suction filtration, which was used to carry out efficient esterification reaction at room temperature.

Benefits of technology

The esterification reaction is quickly completed at room temperature, with the reactant conversion rate up to 100%, and there is no need to separate the catalyst and product, which significantly improves the reaction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119565589A_ABST
    Figure CN119565589A_ABST
Patent Text Reader

Abstract

The invention provides a niobium titanic acid membrane catalytic material for efficiently synthesizing acetate spices at room temperature, which is characterized in that niobium titanic acid nanosheets with a specific number of acid sites are obtained by means of acid treatment and organic alkali intercalation stripping; niobium titanic acid membrane catalytic materials with different numbers of acidic sites are prepared by using a vacuum suction filtration method, and can be used for esterification reaction to synthesize acetate spices; the esterification reaction is carried out in a continuous mobile phase mode, reaction raw materials react in an interlayer confinement channel of a membrane catalytic material, a product flows out along with the mobile phase, and the rapid esterification reaction is realized under the condition of room temperature. Compared with a bulk phase reaction, the method has the advantages that the reaction temperature (23 DEG C) and the reaction duration (lt; the reaction efficiency is greatly improved, the reactant conversion rate can reach 100%, and the catalyst and the product do not need to be separated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of membrane catalysis, and in particular to a niobium titanate membrane catalytic material and a preparation method thereof, and application thereof in the efficient catalytic synthesis of acetate flavors at room temperature. Background Art

[0002] Benzyl acetate is an ester fragrance with a strong jasmine aroma. It exists in many natural essential oils and is the main component of hyacinth, jasmine, gardenia and other essential oils. Its pure product is used to prepare jasmine essence and soap essence; ordinary products are used as solvents for resins or for making spray paints, inks, etc. Therefore, benzyl acetate is a widely used fine chemical product.

[0003] There are usually two methods for preparing benzyl acetate in industry. One is to use benzyl chloride and acetic acid as raw materials and use phase transfer catalyst for catalytic synthesis; the other is to use sulfuric acid as catalyst and esterify acetic acid and benzyl alcohol. In the former, it is difficult to separate the catalyst from the product, and benzyl chloride is highly toxic, which seriously pollutes the environment and affects the health of operators. The latter is a relatively mature process for the industrial production of benzyl acetate, but sulfuric acid catalysis has many side reactions, low reaction yield, poor product quality, complex post-processing process, easy to cause environmental pollution, and serious corrosion of equipment, high maintenance costs, which does not conform to the concept of green chemistry.

[0004] Over the years, people have devoted themselves to the research of esterification catalysts. Currently, seven types of catalysts for synthesizing benzyl acetate have been successfully developed, including solid superacids, organic acids, inorganic salts, ion exchange resins, zeolite molecular sieves, phase transfer catalysts, and niobic acid. However, zeolite molecular sieves have low activity and small pore size; ion exchange resins have poor thermal stability; the preparation process of solid superacids is complicated, and the reaction requires high temperature activation, which is troublesome to handle; other catalysts also have various problems, which greatly hinder the industrial production of benzyl acetate. In addition, most of the catalysts for synthesizing benzyl acetate currently have the disadvantages of requiring heating (50-130°C), long reaction time (>3 hours), and low esterification rate (60-90%) during the esterification reaction. Summary of the invention

[0005] In order to improve the shortcomings of the existing esterification reaction, such as high reaction temperature, long reaction time, low reactant conversion rate and the need to separate and purify the reaction products, the present invention provides a niobium titanate film catalyst material for efficiently synthesizing acetate flavors at room temperature, and a preparation method and use thereof; the present invention first synthesizes potassium niobium titanate blocks by high-temperature calcination; then obtains niobium titanate nanosheets by acid treatment and small molecule intercalation and exfoliation; and then obtains the niobium titanate film catalyst material by vacuum filtration; when the niobium titanate film catalyst material is used for a continuous mobile phase reaction driven by a pressure difference, the reaction raw materials pass through the interlayer channels of the niobium titanate film catalyst material and react efficiently, the products flow out with the mobile phase and leave the system, and finally the esterification reaction is quickly achieved at room temperature, and the reactant conversion rate can reach 100%.

[0006] The object of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a niobium titanate film catalyst material, the method comprising the following steps:

[0008] 1) mixing titanium dioxide, niobium pentoxide and potassium carbonate, and calcining to prepare potassium niobate titanate blocks;

[0009] 2) mixing the potassium niobate titanate block obtained in step 1) with an acid solution, reacting the mixture to prepare niobium titanate;

[0010] 3) mixing the aqueous solution of niobium titanate and the organic base intercalation agent in step 2), and collecting the solid component by centrifugation; mixing the obtained solid component with deionized water, shaking and peeling, and collecting the supernatant by centrifugation to prepare a dispersion of niobium titanate nanosheets;

[0011] 4) The dispersion of the niobium titanate nanosheets in step 3) is subjected to vacuum filtration to form a membrane, and then dried to obtain the niobium titanate membrane catalytic material.

[0012] According to an embodiment of the present invention, in step 1), the molar ratio of titanium dioxide, niobium pentoxide and potassium carbonate is 2:1:1.

[0013] According to an embodiment of the present invention, in step 1), the calcination includes a first calcination and a second calcination, the temperature of the first calcination is 800-1200°C, the time of the first calcination is 2-6h, and the atmosphere of the first calcination is an air atmosphere; the temperature of the second calcination is 800-1200°C, the time of the second calcination is 18-24h, and the atmosphere of the second calcination is an air atmosphere.

[0014] For example, the temperature of the first calcination is 800°C, 900°C, 1000°C, 1100°C or 1200°C; the time of the first calcination is 2h, 3h, 4h, 5h or 6h. The temperature of the second calcination is 800°C, 900°C, 1000°C, 1100°C or 1200°C; the time of the second calcination is 18h, 19h, 20h, 21h, 22h, 23h or 24h.

[0015] According to an embodiment of the present invention, in step 1), after the first calcination is completed, a process step of grinding the material after the first calcination is also included. The purpose of such treatment is to fully calcine the reaction raw materials to form potassium niobate titanate (KNbTiO5) blocks.

[0016] According to an embodiment of the present invention, in step 2), the acid solution is an aqueous hydrochloric acid solution.

[0017] According to an embodiment of the present invention, in step 2), the molar ratio of potassium niobate titanate and acid is 1:5-15, for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14 or 1:15.

[0018] According to an embodiment of the present invention, in step 2), the concentration of the acid solution is, for example, 0.5-3 mol / L, for example, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L or 3 mol / L.

[0019] According to an embodiment of the present invention, in step 2), the reaction is carried out at room temperature.

[0020] According to an embodiment of the present invention, in step 2), the reaction time is not particularly defined. For example, potassium ions in potassium niobate titanate (KNbTiO5) blocks can be removed to obtain niobium titanate (HNbTiO5). The potassium niobate titanate (KNbTiO5) blocks can be fully acidified and surface treated by acidification, providing a basis for obtaining highly active niobium titanate nanosheets.

[0021] According to an embodiment of the present invention, in step 2), the reaction is carried out under stirring conditions.

[0022] According to an embodiment of the present invention, in step 2), after the reaction is completed, post-processing steps such as centrifugation, washing, and drying are also included. Exemplarily, the centrifugation is, for example, to perform solid-liquid separation on the mixed system after acidification by centrifugation, and collect the solid component, which is niobium titanate (HNbTiO5). The washing is, for example, to wash the collected solid component with deionized water. The drying is, for example, to dry the washed solid component at a temperature of 80°C for 12 hours.

[0023] According to an embodiment of the present invention, in step 2), the niobium titanate is a niobium titanate block.

[0024] According to an embodiment of the present invention, the method further comprises repeating step 2) one or more times.

[0025] The study found that repeated acidification treatment is more conducive to removing potassium ions from potassium niobate titanate (KNbTiO5) blocks to obtain niobium titanate (HNbTiO5) blocks.

[0026] According to an embodiment of the present invention, in step 3), the organic base intercalant is selected from organic ammonium hydroxide molecules, and the organic ammonium hydroxide molecules are selected from tetrabutylammonium hydroxide and / or tetraethylammonium hydroxide.

[0027] According to an embodiment of the present invention, in step 3), the mixing is performed under stirring conditions.

[0028] According to an embodiment of the present invention, in step 3), the mixing time is 1-24 h, for example, 2 h, 4 h, 5 h, 6 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h or 24 h.

[0029] According to an embodiment of the present invention, in step 3), the concentration of the aqueous solution of the organic base intercalant is 5-20wt%, for example, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%.

[0030] According to an embodiment of the present invention, in step 3), the molar ratio of the niobium titanate to the organic base intercalant is 1:0.25-1.5, for example, 1:0.25, 1:0.5, 1:0.75, 1:1, 1:1.25 or 1:1.5.

[0031] According to an embodiment of the present invention, in step 3), during the mixing process of the aqueous solution of niobium titanate and the organic base intercalant, the organic base intercalant can be inserted into the niobium titanate block, which is beneficial to expand the multi-layer structure of niobium titanate nanosheets in the niobium titanate block to obtain single-layer niobium titanate nanosheets.

[0032] According to an embodiment of the present invention, in step 3), the shaking peeling is performed on a shaking table.

[0033] According to an embodiment of the present invention, in step 3), the shaking and peeling time is 7-21 days, for example, 7 days, 10 days, 14 days, 15 days, 18 days or 21 days.

[0034] According to an embodiment of the present invention, in step 3), after the shaking and peeling, an aqueous solution containing completely peeled niobium titanate nanosheets and incompletely peeled niobium titanate blocks is obtained. The completely peeled niobium titanate nanosheets include single-layer niobium titanate nanosheets.

[0035] According to an embodiment of the present invention, in step 3), the centrifugation is to separate the mixed system after shaking and peeling, and the obtained supernatant is a dispersion of completely peeled niobium titanate nanosheets, and the obtained solid component is a block of niobium titanate that is not completely peeled. The centrifugation is, for example, to centrifuge the mixed system after shaking and peeling at 3000 rpm for 5 minutes.

[0036] According to an embodiment of the present invention, in step 3), the dispersion of niobium titanate nanosheets includes deionized water and niobium titanate nanosheets; the niobium titanate nanosheets are completely peeled niobium titanate nanosheets, that is, single-layer niobium titanate nanosheets; the sheet diameter of the niobium titanate nanosheets is >300nm.

[0037] According to an embodiment of the present invention, in step 3), the concentration of the dispersion of niobium titanate nanosheets is, for example, 0.2-2 mg / mL, for example, 0.2 mg / mL, 0.4 mg / mL, 0.6 mg / mL, 0.8 mg / mL, 1 mg / mL, 1.2 mg / mL, 1.5 mg / mL, 1.8 mg / mL or 2 mg / mL.

[0038] According to the embodiments of the present invention, unless otherwise specified, the terms "completely exfoliated niobium titanate nanosheets", "single-layer niobium titanate nanosheets" and "niobium titanate nanosheets" have the same meaning and refer to single-layer niobium titanate nanosheets obtained after complete exfoliation.

[0039] According to an embodiment of the present invention, in step 4), a vacuum filtration method is used to prepare a membrane formed by stacking multiple niobium titanate nanosheets of a certain thickness on a porous substrate.

[0040] According to an embodiment of the present invention, the porous substrate may be made of an organic filter membrane such as nylon 66, polyvinylidene fluoride, polytetrafluoroethylene, etc. The pore size of the porous substrate is 0.1-0.3 μm, for example, 0.22 μm.

[0041] According to an embodiment of the present invention, in step 4), the drying is carried out at room temperature or under heating conditions, and the heating temperature is 40-120°C, for example, 40°C, 60°C, 80°C, 100°C or 120°C; the drying time is 3-24 hours, for example, 6 hours, 8 hours, 10 hours, 12 hours, 15 hours or 18 hours.

[0042] According to an embodiment of the present invention, in step 4), the dispersion of niobium titanate nanosheets is added to a filter cup of a vacuum filtration device, and the vacuum pump is started to perform vacuum filtration with a vacuum degree of 1-5 Pa. As the filtration proceeds, the niobium titanate nanosheets in the dispersion of niobium titanate nanosheets are assembled into a layered structure under the action of water flow, and when the filtration is completed, a niobium titanate film catalyst material is obtained.

[0043] The present invention also provides a niobium titanate film catalyst material prepared by the above method.

[0044] According to an embodiment of the present invention, the niobium titanate film catalytic material is a layered structure formed by stacking niobium titanate nanosheets, preferably a layered structure formed by stacking a plurality of niobium titanate nanosheets, wherein the diameter of the niobium titanate nanosheets is greater than 300 nm.

[0045] According to an embodiment of the present invention, the interlayer spacing of the niobium titanate film catalyst material is 1.0nm-1.8nm, for example, 1.0nm, 1.1nm, 1.2nm, 1.3nm, 1.4nm, 1.5nm, 1.6nm, 1.7nm or 1.8nm. The interlayer spacing of the niobium titanate film catalyst material is regulated by regulating the size of the organic base intercalation agent or removing the bound water between the layers of the niobium titanate film catalyst material by heating. For example, the higher the drying temperature, the smaller the interlayer spacing of the obtained niobium titanate film catalyst material.

[0046] According to an embodiment of the present invention, the thickness of the niobium titanate film catalyst material is 0.5-12μm, for example, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm; the thickness of the niobium titanate film catalyst material can be adjusted by adjusting the concentration of the niobium titanate nanosheet dispersion or the filtration volume of the dispersion. The greater the concentration of the niobium titanate nanosheet dispersion or the larger the filtration volume of the dispersion, the thicker the thickness of the obtained niobium titanate film catalyst material, and the smaller the concentration of the niobium titanate nanosheet dispersion or the smaller the filtration volume of the dispersion, the thinner the thickness of the obtained niobium titanate film catalyst material. A membrane catalytic material that is too thin will easily crack during the subsequent reaction process, and the reaction raw materials will separate from the membrane catalytic material before they have time to react, resulting in a lower conversion rate; while a membrane catalytic material that is too thick will require a long vacuum filtration time and will easily introduce too many defects during the preparation process, reducing the orderliness of the two-dimensional confined space provided for the reaction molecules.

[0047] According to an embodiment of the present invention, the niobium titanate film catalytic material is used for esterification reaction.

[0048] According to an embodiment of the present invention, the niobium titanate film catalytic material is used to catalyze the esterification reaction of alcohol substances and acetic anhydride.

[0049] According to an embodiment of the present invention, the alcohol substance includes at least one of benzyl alcohol, 4-methylbenzyl alcohol, 4-methoxybenzyl alcohol, phenylethyl alcohol, cinnamyl alcohol, 1-phenylethyl alcohol, isopentanol, cyclohexanol, 4-nitrobenzyl alcohol and 4-chlorobenzyl alcohol.

[0050] The present invention also provides the use of the niobium titanate film catalytic material in an esterification reaction.

[0051] According to an embodiment of the present invention, the niobium titanate film catalyst material is used in catalyzing the esterification reaction of alcohol substances and acetic anhydride.

[0052] The present invention also provides a method for esterification reaction, which comprises the following steps:

[0053] a) mixing an alcohol substance, acetic anhydride and a solvent to obtain a reaction solution;

[0054] b) driving the reaction solution of step a) through the above-mentioned niobium titanate film catalyst material by pressure difference to carry out esterification reaction.

[0055] According to an embodiment of the present invention, in step a), the alcohol substance includes at least one of benzyl alcohol, 4-methylbenzyl alcohol, 4-methoxybenzyl alcohol, phenylethyl alcohol, cinnamyl alcohol, 1-phenylethyl alcohol, isopentanol, cyclohexanol, 4-nitrobenzyl alcohol and 4-chlorobenzyl alcohol.

[0056] According to an embodiment of the present invention, in step a), the solvent is selected from acetonitrile.

[0057] According to an embodiment of the present invention, in step a), the molar ratio of the alcohol substance to acetic anhydride is 1:0.5-2.5, for example, 1:0.5, 1:0.75, 1:1, 1:1.25, 1:1.5, 1:2 or 1:2.5.

[0058] According to an embodiment of the present invention, in step b), the esterification reaction is carried out in a continuous mobile phase reaction mode driven by pressure difference, and the alcohol molecules and acetic anhydride molecules react efficiently in the interlayer confined channels of the membrane catalytic material, and the products flow out with the mobile phase and leave the system.

[0059] According to an embodiment of the present invention, in step b), the temperature of the esterification reaction is room temperature, and the room temperature refers to a temperature range of 20 to 30°C, for example, 23°C.

[0060] According to an embodiment of the present invention, in step b), the esterification reaction time is 2-60s, such as 2-30s.

[0061] According to an embodiment of the present invention, in step b), the pressure difference is greater than or equal to 1 atm.

[0062] Beneficial effects of the present invention:

[0063] The present invention provides a niobium titanate film catalytic material for efficiently synthesizing acetate flavors at room temperature. Niobium titanate nanosheets with a specific number of acid sites are obtained by acid treatment and organic base intercalation stripping, and niobium titanate film catalytic materials with different numbers of acid sites are prepared by vacuum filtration, which can be used for esterification reaction to synthesize acetate flavors; the esterification reaction is carried out in a continuous mobile phase, the reaction raw materials react in the interlayer confined channel of the membrane catalytic material, and the product flows out with the mobile phase, and a rapid esterification reaction is achieved at room temperature. Compared with the bulk reaction, the present invention optimizes the reaction temperature (23°C) and the reaction time (<30s), greatly improves the reaction efficiency, the reactant conversion rate can reach 100%, and there is no need to separate the catalyst and the product. Further, by adjusting the acid strength of the niobium titanate film catalytic material (by selecting different types of organic base intercalation agents) and the temperature of the drying treatment, it is suitable for the esterification of different reactive molecules to synthesize different acetate flavors. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Figure 1 It is a transmission electron microscope image of the niobium titanate nanosheets prepared in Example 1 of the present invention and a scanning electron microscope cross-sectional image of the niobium titanate film catalyst material prepared in Example 7.

[0065] Figure 2 These are X-ray diffraction patterns of the niobium titanate film catalyst materials prepared in Examples 2 and 5-7 of the present invention after drying at different temperatures.

[0066] Figure 3 The attenuated total reflection infrared spectra of the niobium titanate film catalyst materials prepared in Examples 2 and 5-7 of the present invention after drying at different temperatures.

[0067] Figure 4 It is a structural schematic diagram of a membrane reaction device described in a preferred embodiment of the present invention. DETAILED DESCRIPTION

[0068] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0069] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0070] The calculation method of the reaction conversion mentioned in the following examples and comparative examples is as follows:

[0071] The collected liquid through the membrane is quantitatively analyzed by hydrogen nuclear magnetic resonance spectrum to calculate the reaction conversion rate, which specifically includes the following steps:

[0072] After the reaction is completed, acetonitrile is added to the filter bottle to dissolve the product and obtain the product collection liquid. Part of the collection liquid is taken into a 10mL flask, and the acetonitrile solvent is removed by rotary evaporation at 50°C. Deuterated dimethyl sulfoxide (C2D6SO) is used to prepare the NMR sample. There are characteristic hydrogens in both the reactant and product molecules. There is a corresponding relationship between the characteristic hydrogen and the number of molecules. The integral area of ​​the single peak at different chemical shifts is compared by single peak fitting calculation, the corresponding molecular number ratio is calculated, and then the reaction conversion rate is calculated.

[0073] The mass of the membrane involved in the reaction in the following examples can be calculated by the following formula:

[0074]

[0075] Among them, C is the concentration of niobium titanate nanosheet dispersion (in mg / mL); V is the volume of niobium titanate nanosheet dispersion (in mL); D is the diameter of the modified membrane, which is 40 mm; d is the diameter of the actual reaction liquid passing through the membrane, which is 15 mm. Substituting the two into the above test, we can get m≈0.1406×C×V.

[0076] Preparation Example 1

[0077] 1) Weigh 6.25 g of titanium dioxide, 10.23 g of niobium pentoxide, and 5.58 g of potassium carbonate respectively, grind and mix them evenly, place them in a muffle furnace and calcine them at 1000°C for 4 h, and collect samples; grind and mix the collected samples again, then place them in a muffle furnace and calcine them at 1000°C for 20 h, collect samples, and grind them to obtain potassium niobate titanate (KNbTiO5).

[0078] 2) Weigh 2 g of potassium niobium titanate prepared in step 1), add it to 500 mL of hydrochloric acid solution (1 mol / L), stir for 3 days, then centrifuge, wash with water, collect the solid powder, and place the obtained powder in an oven at 80°C to dry for 12 hours; repeat the above steps 3 times to obtain niobium titanate (HNbTiO5) solid powder.

[0079] 3) Weigh 500 mg of the niobium titanate solid powder prepared in step 2), add 100 mL of tetrabutylammonium hydroxide aqueous solution (10 wt%), stir for 6 hours, and collect the solid sample by centrifugation; disperse the obtained solid sample again in 500 mL of deionized water, place it on a shaker, and shake and peel it for 14 days to obtain a niobium titanate aqueous solution.

[0080] 4) The niobium titanate aqueous solution obtained in step 3) was centrifuged at 3000 rpm for 5 minutes to remove the incompletely peeled blocks, and the supernatant finally obtained was the niobium titanate nanosheet (HNbTiO5NS) dispersion (concentration of about 0.6 mg / mL).

[0081] Comparative Example 1

[0082] The niobium titanate nanosheet dispersion prepared in Preparation Example 1 was centrifuged at 12,000 rpm for 8 minutes, and the lower solid layer was vacuum dried at 60° C. for 12 hours to finally obtain niobium titanate nanosheet powder.

[0083] The dried niobium titanate nanosheet powder was used to catalyze the esterification reaction of benzyl alcohol and acetic anhydride. The specific operation was as follows: benzyl alcohol (2 mmol) was weighed and added to 10 mL of acetonitrile, and acetic anhydride (3 mmol) was added at the same time and mechanically stirred for 3 minutes to obtain a reaction solution; 10 mg of niobium titanate nanosheet powder was weighed and added to the above reaction solution, and mechanical stirring was maintained. The reaction temperature was controlled by an oil bath constant temperature magnetic stirrer and controlled to 60°C; after reacting for 24 hours, 2.0 mL of the above reaction solution was sampled, the solvent was removed by rotary evaporation, the concentrate was dissolved with deuterated dimethyl sulfoxide, and then 1 The components were analyzed by HNMR spectroscopy and the conversion and selectivity were determined.

[0084] The reaction results were as follows: the reaction temperature was 60° C., the reaction time was 24 hours, and the conversion rate was 83.7%.

[0085] Comparative Example 2

[0086] The other operations are the same as those in Comparative Example 1, except that:

[0087] The temperature of the esterification reaction of benzyl alcohol and acetic anhydride was controlled to be 40°C.

[0088] The reaction results were as follows: the reaction temperature was 40° C., the reaction time was 24 hours, and the conversion rate was 45.4%.

[0089] Comparative Example 3

[0090] The other operations are the same as those in Comparative Example 1, except that:

[0091] The temperature of the esterification reaction of benzyl alcohol and acetic anhydride was controlled to be 23°C.

[0092] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was 24 hours, and the conversion rate was 21.3%.

[0093] Example 1

[0094] Take 10 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 60°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 0.84 mg (thickness 2.61 μm).

[0095] The dried niobium titanate film catalyst material is used to catalyze the esterification reaction of benzyl alcohol and acetic anhydride. The specific operation is as follows: fix and seal the niobium titanate film catalyst material in a micro-filtration device. Then, add 10mL of acetonitrile reaction solution containing benzyl alcohol (2mmol) and acetic anhydride (3mmol) into the measuring cylinder above the filtration device. Driven by the pressure difference (1atm), the reaction solution passes through the two-dimensional channel between the layers of the membrane, the reactants react between the layers, and the product flows out with the solvent. The solvent is removed by rotary evaporation, and the concentrate is dissolved with deuterated dimethyl sulfoxide, and then 1 The components were analyzed by HNMR spectroscopy and the conversion rate was determined.

[0096] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 23.6%.

[0097] Example 2

[0098] Other operations are the same as those in Example 1, except that:

[0099] Take 20 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 60°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 1.68 mg (thickness 5.22 μm).

[0100] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 62.3%.

[0101] Example 3

[0102] Other operations are the same as those in Example 1, except that:

[0103] Take 30 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 60°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 2.52 mg (thickness 7.83 μm).

[0104] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 85.3%.

[0105] Example 4

[0106] Other operations are the same as those in Example 1, except that:

[0107] Take 40 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 60°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 3.36 mg (thickness of 10.44 μm).

[0108] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 100%.

[0109] Example 5

[0110] Other operations are the same as those in Example 1, except that:

[0111] Take 20 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 40°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 1.68 mg (thickness 5.52 μm).

[0112] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 56.1%.

[0113] Example 6

[0114] Other operations are the same as those in Example 1, except that:

[0115] Take 20 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 80°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 1.68 mg (thickness 4.97 μm).

[0116] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 78.5%.

[0117] Example 7

[0118] Other operations are the same as those in Example 1, except that:

[0119] Take 20 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 100°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 1.68 mg (thickness 3.92 μm).

[0120] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 100%.

[0121] Example 8

[0122] Other operations are the same as those in Example 1, except that:

[0123] Take 20 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 100°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 1.68 mg (thickness 3.92 μm).

[0124] The dried niobium titanate film catalyst material is used to catalyze the esterification reaction of p-methylbenzyl alcohol and acetic anhydride. The specific operation is as follows: fix and seal the niobium titanate film catalyst material in a micro-filtration device. Then, add 10mL of acetonitrile reaction solution containing p-methylbenzyl alcohol (2mmol) and acetic anhydride (3mmol) into the measuring cylinder above the filtration device. Driven by the pressure difference (1atm), the reaction solution passes through the two-dimensional channel between the layers of the membrane, the reactants react between the layers, and the products flow out with the solvent. The solvent is removed by rotary evaporation, and the concentrate is dissolved with deuterated dimethyl sulfoxide, and then 1 The components were analyzed by HNMR spectroscopy and the conversion rate was determined.

[0125] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 100%.

[0126] Example 9

[0127] Other operations are the same as those in Example 1, except that:

[0128] Take 20 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 100°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 1.68 mg (thickness 3.92 μm).

[0129] The dried niobium titanate film catalyst material is used to catalyze the esterification reaction of p-methoxybenzyl alcohol and acetic anhydride. The specific operation is as follows: fix and seal the niobium titanate film catalyst material in a micro-filtration device. Then, add 10mL of acetonitrile reaction solution containing p-methoxybenzyl alcohol (2mmol) and acetic anhydride (3mmol) into the measuring cylinder above the filtration device. Driven by the pressure difference (1atm), the reaction solution passes through the two-dimensional channel between the layers of the membrane, the reactants react between the layers, and the products flow out with the solvent. The solvent is removed by rotary evaporation, and the concentrate is dissolved with deuterated dimethyl sulfoxide, and then 1 The components were analyzed by HNMR spectroscopy and the conversion rate was determined.

[0130] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 100%.

[0131] Example 10

[0132] Other operations are the same as those in Example 1, except that:

[0133] Take 20 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 100°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 1.68 mg (thickness 3.92 μm).

[0134] The dried niobium titanate film catalyst material is used to catalyze the esterification reaction of phenylethanol and acetic anhydride. The specific operation is as follows: fix and seal the niobium titanate film catalyst material in a micro-filtration device. Then, add 10mL of acetonitrile reaction solution containing phenylethanol (2mmol) and acetic anhydride (3mmol) into the measuring cylinder above the filtration device. Driven by the pressure difference (1atm), the reaction solution passes through the two-dimensional channel between the layers of the membrane, the reactants react between the layers, and the products flow out with the solvent. The solvent is removed by rotary evaporation, and the concentrate is dissolved with deuterated dimethyl sulfoxide, and then 1 The components were analyzed by HNMR spectroscopy and the conversion rate was determined.

[0135] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 100%.

[0136] Embodiment 11

[0137] Other operations are the same as those in Example 1, except that:

[0138] Take 20 mL of the niobium titanate nanosheet dispersion prepared in Preparation Example 1 and prepare a membrane by vacuum filtration (vacuum degree 1 atm). After the water above the membrane is drained, remove the membrane from the filtration device and place it in a watch glass and dry it at 100°C for 10 hours to obtain a niobium titanate membrane catalytic material with a mass of 1.68 mg (thickness 3.92 μm).

[0139] The dried niobium titanate film catalyst material is used to catalyze the esterification reaction of cinnamyl alcohol and acetic anhydride. The specific operation is as follows: fix and seal the niobium titanate film catalyst material in a micro-filtration device. Then, add 10mL of acetonitrile reaction solution containing cinnamyl alcohol (2mmol) and acetic anhydride (3mmol) into the measuring cylinder above the filtration device. Driven by the pressure difference (1atm), the reaction solution passes through the two-dimensional channel between the layers of the membrane, the reactants react between the layers, and the products flow out with the solvent. The solvent is removed by rotary evaporation, and the concentrate is dissolved with deuterated dimethyl sulfoxide, and then 1 The components were analyzed by HNMR spectroscopy and the conversion rate was determined.

[0140] The reaction results were as follows: the reaction temperature was 23° C., the reaction time was less than 1 minute, and the conversion rate was 100%.

[0141] Figure 1 The transmission electron microscope image of the niobium titanate nanosheet prepared in Example 1 of the present invention and the scanning electron microscope cross-sectional image of the niobium titanate film prepared in Example 7 are shown in FIG. Figure 1 As can be seen from a in Figure 1, niobium titanate nanosheets are ultra-thin sheets with a size greater than 300 nanometers. Figure 1 As can be seen in b, the niobium titanate film is composed of stacked niobium titanate nanosheets.

[0142] Figure 2 The X-ray diffraction diagrams of the niobium titanate film catalyst materials prepared in Examples 2, 5-7 of the present invention after drying at different temperatures. Figure 2 It can be seen that as the drying temperature increases, the interlayer distance (d) of the niobium titanate film catalyst material gradually decreases. This can also be verified from the niobium titanate film catalyst materials of equal mass obtained in Examples 2, 5-7, but with different thicknesses.

[0143] Figure 3 The attenuated total reflection infrared spectra of the niobium titanate film catalyst materials prepared in Examples 2, 5-7 of the present invention after drying at different temperatures. Figure 3 It can be seen that the peak positions of the prepared niobium titanate nanosheets remain basically unchanged after drying at different temperatures, indicating their excellent stability. -1 and 1600cm -1 There are strong absorption peaks on the left and right, indicating the presence of hydroxyl groups on the surface of niobium titanate nanosheets.

[0144] Table 1 is a comparison table of reaction temperature, reaction time and yield of the niobium titanate film catalyst material of the present invention and the catalytic benzyl acetate synthesis reported in the literature. As can be seen from Table 1, in order to improve the conversion rate, the catalytic benzyl acetate synthesis process reported in the literature generally requires a relatively high reaction temperature (40-110°C) or reaction time (>30min). In contrast, the niobium titanate film catalyst material of the present invention can greatly improve the reaction efficiency and optimize the reaction temperature (23°C) and reaction time (<30s).

[0145]

[0146] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a niobium titanate film catalyst material, the method comprising the following steps: 1) mixing titanium dioxide, niobium pentoxide and potassium carbonate, and calcining to prepare potassium niobate titanate blocks; 2) mixing the potassium niobate titanate block obtained in step 1) with an acid solution, reacting the mixture to prepare niobium titanate; 3) mixing the aqueous solution of niobium titanate and the organic base intercalation agent in step 2), and collecting the solid component by centrifugation; mixing the obtained solid component with deionized water, shaking and peeling, and collecting the supernatant by centrifugation to prepare a dispersion of niobium titanate nanosheets; 4) The dispersion of the niobium titanate nanosheets in step 3) is subjected to vacuum filtration to form a membrane, and then dried to obtain the niobium titanate membrane catalytic material.

2. The preparation method according to claim 1, wherein In step 1), the molar ratio of titanium dioxide, niobium pentoxide and potassium carbonate is 2:1:1; And / or, in step 1), the calcination includes a first calcination and a second calcination, the temperature of the first calcination is 800-1200°C, the time of the first calcination is 2-6h, and the atmosphere of the first calcination is an air atmosphere; the temperature of the second calcination is 800-1200°C, the time of the second calcination is 18-24h, and the atmosphere of the second calcination is an air atmosphere.

3. The preparation method according to claim 1 or 2, wherein In step 2), the acid solution is an aqueous solution of hydrochloric acid; And / or, in step 2), the molar ratio of potassium niobate titanate to acid is 1:5-15.

4. The preparation method according to any one of claims 1 to 3, wherein: In step 3), the organic base intercalant is selected from organic ammonium hydroxide molecules, and the organic ammonium hydroxide molecules are selected from tetrabutylammonium hydroxide and / or tetraethylammonium hydroxide; and / or, in step 3), the concentration of the aqueous solution of the organic base intercalation agent is 5-20 wt %; And / or, in step 3), the molar ratio of the niobium titanate to the organic base intercalation agent is 1:0.25-1.5; And / or, in step 3), the dispersion of niobium titanate nanosheets comprises deionized water and niobium titanate nanosheets; And / or, in step 3), the concentration of the dispersion of niobium titanate nanosheets is, for example, 0.2-2 mg / mL.

5. The preparation method according to any one of claims 1 to 4, wherein: In step 4), a film formed by stacking a plurality of niobium titanate nanosheets of a certain thickness is prepared on a porous substrate by a vacuum filtration method; And / or, in step 4), the drying is carried out at room temperature or under heating conditions, the heating temperature is 40-120° C.; the drying time is 3-24 hours.

6. The niobium titanate film catalyst material prepared by the method according to any one of claims 1 to 5.

7. The membrane catalytic material according to claim 6, wherein: The niobium titanate film catalytic material is a layered structure formed by stacking niobium titanate nanosheets; And / or, the interlayer spacing of the niobium titanate film catalyst material is 1.0nm-2.0nm; And / or, the thickness of the niobium titanate film catalyst material is 0.5-12 μm.

8. Use of the niobium titanate film catalyst material according to claim 6 or 7 in an esterification reaction. Preferably, the niobium titanate film catalyst material is used in catalyzing the esterification reaction of alcohol substances and acetic anhydride.

9. A method for esterification reaction, comprising the steps of: a) mixing an alcohol substance, acetic anhydride and a solvent to obtain a reaction solution; b) driving the reaction solution of step a) through the niobium titanate film catalyst material of claim 6 or 7 by pressure difference to carry out esterification reaction.

10. The method according to claim 9, wherein: In step a), the alcohol substance comprises at least one of benzyl alcohol, 4-methylbenzyl alcohol, 4-methoxybenzyl alcohol, phenylethyl alcohol, cinnamyl alcohol, 1-phenylethyl alcohol, isopentanol, cyclohexanol, 4-nitrobenzyl alcohol and 4-chlorobenzyl alcohol; And / or, in step a), the solvent is selected from acetonitrile; And / or, in step a), the molar ratio of the alcohol substance to acetic anhydride is 1:0.5-2.

5. According to an embodiment of the present invention, in step b), the temperature of the esterification reaction is room temperature. And / or, in step b), the esterification reaction time is 2-60s. And / or, in step b), the pressure difference is greater than or equal to 1 atm.